Water governance for resilience to climate change - Kjellen, M.; White, M.; Matthews, J.; Mauroner, A.; Timboe, I.; Burchi, S.; Dhot, N.; Waeyenberge, T. van; El Fenni, Y. R.; Lohani, A.; Newton, J.; Imamura, Y.; et al. (2020)
This chapter outlines legal, institutional and political means to support climate change adaptation and mitigation, to enhance resilience, and to reduce vulnerability through more inclusive water management, especially at the country level.